Active pharmaceutical ingredients (APIs) in ionic liquids: An effective approach for API physiochemical parameter optimization. Issue 9 (September 2022) - Handa, Mayank; Almalki, Waleed H.; Shukla, Rahul; Afzal, Obaid; Altamimi, Abdulmalik Saleh Alfawaz; Beg, Sarwar; Rahman, Mahfoozur
Highlights: Ionic liquids (ILs) are ions-based substances with melting points below 100 °C. Versatile nature and properties of ILs made it as solvent and designer solvents. Depending upon the properties, ILs are categorized into three different generations. Third-generation ILs have low cost, biodegradable, and possess lesser toxicity. API-ILs observed higher solubility, bioavailability and therapeutics over APIs. Abstract : Ionic liquids (ILs) are widely used as solvents, co-solvents and permeation enhancers in the biomedical and pharmaceutical fields. There are many advantages to using active pharmaceutical ingredients (APIs) in the production of ILs for drug delivery, including the ability to tailor solubility, improve thermal stability, increase dissolution, regulate drug release, improve API permeability, and modulate cytotoxicity on tumor cells. Such an approach has shown significant potential as a tool for drug delivery. As a result, APIs converted into ILs are used as active components in solutions, emulsions, and even nanoparticles (NPs). In this review, we explore the use and physiochemical characteristics of APIs via ILs, including improvements of their physicochemical properties in preformulation and formulation development.